Informant discrepancies in child maltreatment reporting: a systematic review - Cooley, Daryl T. (Child maltreatment, 2022)
Potential informants on child maltreatment include the youth who has experienced the alleged maltreatment, and the youth’s caregivers, social workers and case files. When multiple informants are compared, they often disagree about whether or not a youth has experienced maltreatment. Such determinations are critical as endorsement—or lack of endorsement—of maltreatment can have significant consequences on the child’s safety, future living arrangements and referral for treatment and services. The current study provides a systematic review of the literature on informant discrepancies in child maltreatment. Three databases—PsychINFO, Web of Science, and PubMed—were used to identify studies for the review and 13 articles met inclusion criteria. Results showed that more youth tend to report physical, sexual and emotional abuse than seen in case files. By contrast, more case files include neglect than reported by youth. Implications and future directions are discussed.